Carbon doped solid solution Bi0.5Dy0.5VO4 for efficient photocatalytic hydrogen evolution from water. (28th September 2016) - Wang, Qizhao; Jiao, Danhua; Wu, Yanxia; Guo, Hao; She, Houde; Li, Jianzhang; Zhong, Junbo; Wang, Fangping; Tong, Jinhui
Abstract: In this study, carbon doped Bi0.5 Dy0.5 VO4 solid solution was prepared and characterized by X-ray diffractometry (XRD), Scanning electron microscopy (SEM), UV–vis diffuse reflectance spectra, and photocurrent density. The as-synthesized sample shows the superior photocatalytic activity of splitting water into hydrogen: the amount of produced hydrogen is 506.3 μmol h −1  g −1 . The enhanced activity could be attributed to the light absorption behavior of the carbon spheres (CSs) and effective separation of photo-generated holes and electrons. Highlights: Carbon doped solid solution Bi0.5 Dy0.5 VO4 (BDV) was successfully synthesized. After doping with carbon spheres, the hydrogen evolution of the samples increased greatly when loaded by 0.5% Pt. The composites of C-BDV possesses a porous structure promising the best photocatalytic property. Electron conductivity of carbon promotes the electron transportation.